PENDIDIKAN KARAKTER DALAM PERSPEKTIF KI HAJAR DEWANTARA - Anisah, Nur (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
The purpose of this study was to determine the concept of character education in the perspective of Ki Hajar Dewantara and their implications in education today. This research was focused on the literary reference books and relevant sources. The data were taken by library research and qualitative approach literature which is a purely literary study, using the method of documentation to find the data on things or variables in the form of notes such like books, magazines, documents, regulations, daily notes, meeting notes, journals and so on. The research found that Ki Hajar Dewantara respected by the people as well his enemy, because he has extensive knowledge and unique thinking. Ki Hajar Dewantara gives hope for the bottom to be able to get an education as well as the national spirit culture homage to his educational concept. Ki Hajar Dewantara has among systems, which educators have a very important role, namely as role models and mentors for the students, so that parents and teachers are required to behave well in front of their students. As pointed out above, it is important to writers to contribute in the form of suggestion, such as Ki Hajar Dewantara’ concept of thought has an applicable relevant concept in the purpose of building and maintaining character education up to now.